Evaluation of Financial Indicators of Construction Firms Listed in the Hanoi Stock Exchange - Nguyen Dieu Linh; Nguyen Thị Thanh Nga (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The main purpose of this study is to empirically test financial indicators of construction firms Listed in the Hanoi Stock Exchange (HNX). For this purpose, in this study we evaluate three (3) financial indicators of construction firms listed in the Hanoi stock exchange, including (i) Receivable turnover ratio (RT); (ii) Inventory turnover ratio (IT) and (iii) Payable turnover ratio (PT). The results of the research show that financial indicators of construction firms have many significant differences. Therefore, managers may enhance the firm performance of their firms by specific measures and construction firms need to focus on measures to improve receivables turnover, inventory turnover and payable turnover ratio. This study will benefit the construction firms Listed in HNX in the improvement of their firm performance.